IIUM’s Dr. Maszlee Malik becomes Malaysia’s Education Minister - Hasan, Md. Mahmudul (Office of Corporate Communication, International Islamic University Malaysia, 2018)
Former IIUM academic and MP for Simpang Renggam, Dr. Maszlee Malik was sworn in as Education Minister of Malaysia on 21 May 2018. Before joining active politics, Dr. Maszlee was with IIUM for eighteen years. He was also the President of IIUM Academic Staff Association (ASA) for two terms, from 23 February 2012 to 19 February 2016. Initially, Dr. Maszlee taught Fiqh, Usul al-Fiqh and other Islamic subjects at the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS). However, towards the end of his academic career at IIUM, he taught in the Department of Political Science of the same faculty. His book titled Foundations of Islamic Governance: A Southeast Asian Perspective (2017) is published by Routledge (London) in its Studies on Islam and Muslims in Southeast Asia series.